The role of miRNA200a as biomarker to detect breast and ovarian cancers in Iraqi women (Journal of Pharmaceutical Negative Results, 2022)
MiRNASa(miRNAS)a are small non-codingaRNAS that key post- transcriptionala regulators of gene expression . Breast and ovarian cancers are most a common malignancies among females. The biological function of amiRNA200a has not been elucidated completely. miRNA200aaconsidered as a tumor-suppressor miRNA or oncogenic miRNA. The present study evaluated a the expression of miRNA200a was asignificant low expression in a breast cancer and has shown a the function of tumor-suppressor role. furthermore , the expression of miRNA200a wasa non-significant high expression in a ovarian cancer and has shown the function of a oncogenic role . The dual a role of miRNA200a in a diverse kinds of a tumor has long been attractive.